2012
DOI: 10.1007/s12529-012-9284-8
|View full text |Cite
|
Sign up to set email alerts
|

Depression, Posttraumatic Stress, and Risk Factors Following Spinal Cord Injury

Abstract: Depressive reactions and posttraumatic distress may commonly occur after spinal injuries but will usually improve over time. It might be useful to routinely arrange follow-up contacts post-discharge in order to timely identify patients who are at risk of developing chronic psychopathology and require intervention.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
31
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(36 citation statements)
references
References 33 publications
3
31
2
Order By: Relevance
“…26 The occurrence of depression and PTSD after spinal cord injury was mediated by maladaptive coping style. 27 The sum of maladaptive coping strategy scores (denial, substance use, behavioural disengagement, self-distraction, self-blame) was computed as an indicator of maladaptive coping. The higher the maladaptive coping test score, the more patients habitually use maladaptive coping strategies.…”
Section: Brief Cope Inventorymentioning
confidence: 99%
“…26 The occurrence of depression and PTSD after spinal cord injury was mediated by maladaptive coping style. 27 The sum of maladaptive coping strategy scores (denial, substance use, behavioural disengagement, self-distraction, self-blame) was computed as an indicator of maladaptive coping. The higher the maladaptive coping test score, the more patients habitually use maladaptive coping strategies.…”
Section: Brief Cope Inventorymentioning
confidence: 99%
“…Research on posttraumatic stress following SCI finds prevalence rates of 1% -44% for posttraumatic symptoms [3][4][5][6][7][8][9][10] . This wide disparity in prevalence rates mostly stems from variation in the amount of time-since-injury of the participant sample.…”
mentioning
confidence: 99%
“…This wide disparity in prevalence rates mostly stems from variation in the amount of time-since-injury of the participant sample. Studies of participants with more recent SCIs (3-24 months post-injury) report prevalence rates between 14% -44% [3][4][5] , whereas studies involving participants with more distant SCIs (> 2 years) report prevalence rates of 1% -13% [6][7][8] . However, it should be noted that one study did find a prevalence rate of only 1% in a sample of participants with a recent SCI 9 .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…It was found that nearly half of those with SCI suffered mental health problems of depression, anxiety, clinical-level stress, or PTSD. Furthermore, Schönenberg et al (2012) found that 4 years post discharge from hospital, 2% of individuals with SCI were currently identified with chronic PTSD symptomatology. These authors concluded that depressive symptoms and post-traumatic distress may be common following SCI but improve with time.…”
Section: Introductionmentioning
confidence: 99%